Fikih kerukunan dalam naskah Serat Waosan Puji - Zakiyah, Zakiyah (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2012)
This paper focus on a manuscript entitled Serat Waosan Puji. This manuscript is saved at Widya Budaya library of Yogyakarta kingdom. Data is analyzed using reception theory and sociology of letter. Finding of this research shows that physically this manuscript is in a good condition and readable. This manuscript consists of several texts which tell about doâa (prayer), pillar of faith, pillar of Islam, theology, name of verses in the Quran, Ki Purwadaksinaâs teaching, Serat Niti Sruti, and Serat Nitipraja. Meanwhile, the teaching of harmony is stated in three pupuh (chapter) namely pupuh dhandhanggula consisting of Ki Purwadaksinaâs teaching, pupuh dhandhanggula consisting of Serat Nitisruti, pupuh dhandhanggula consisting of serat Nitipraja. Among all of those harmonius teaching are (1) philosophy of life comprising pandhita lami, pandhita boja karana, and pandhita umarshandu or pandhita gunung, (2) things which should be avoided namely pandhita sipat, limpad, prakken sang hyang, nggenthong umos and tawang brana. (3) lesson of life interaction such as empathy, respecting others, humble and others, (4) asthabrata, (5) principle of king.